Wzmocniona ochrona dóbr kulturalnych w razie konfliktu zbrojnego — propozycja listy polskich obiektów - Jankowska-Sabat, Monika (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The Second Protocol to the Hague Convention of 1954 for the Protection of Cultural Property in the Event of Armed Conflict was adopted in The Hague on 26 March 1999 and entered into force on 9 March 2004. The Polish Republic ratified the Protocol on 17 November. The Protocol came into force in Poland on 3 April 2012. The Protocol established a new system of enhanced protection of cultural property. The granting, suspension and withdrawal of enhanced protection established by the Protocol is decided by the Committee for the Protection of Cultural Property in the Event of Armed Conflict. Enhanced protection is granted to cultural property when it is entered on the List of cultural property under enhanced protection.This article does not discuss the overall content of the Protocol, which is a comprehensive document. It is rather to focus on the issues of the enhanced protection of cultural property in the event of armed conflict. This issue is of particular interest in the context of the protection of Polish goods. In the paper the author proposes a list of Polish sites for which Poland could claim enhanced protection. Two categories of cultural property in Poland aspire to be listed for enhanced protection: 12 cultural properties inscribed on the World Heritage List and historical monuments. Bothgroups of cultural property satisfy the condition of greatest importance for humanity. They are also protected by adequate domestic legal and administrative measures recognizing their exceptional cultural and historic value and ensuring the highest level of protection. The cultural property concerned must not be used for military purposes or to shield military sites. The party which has control over the cultural property has to make a declaration confirming that the cultural property will not be used for military purposes or to shield military sites.
Keywords: Konwencja Haska z 1954 r.; Protokół drugi; ochrona dóbr kultury na wypadek konfliktu zbrojnego; ochrona wzmocniona; ochrona specjalna